Pembuatan Ikan Lele (Clarias gariepinus) Asap Menggunakan Bahan Bakar Arang Kayu dan Sabut Kelapa pada Berbagai Konsentrasi - Asmara, Sandi; Tamrin, Tamrin; Kuncoro, Sapto; Amalia, Anggun Clarisa (Jurnal Agricultural Biosystem Engineering, 2024)
Catfish (Clarias gariepinus) is a type of fish that is widely cultivated in Indonesia. People in Lampung Province really like catfish with a consumption level of 17.10% of total household fish consumption. Catfish have a high water content so they are easily damaged. One way to preserve is smoking. The smoking process uses fuel to produce smoke and uses a drum type smoker. This research aims to determine the type of fumigation fuel that is effective for carrying out fumigation according to SNI quality. The parameters observed were water content, yield, amount of fuel used, and organoplastic tests (appearance, aroma, taste and texture). Then the data was analyzed using Microsoft Excel and continued with the BNT test. The results showed that A3 treatment with a mixture of charcoal and coconut fiber produced the best quality smoked catfish with a water content of 40.54%, with a sensory value of appearance of 8.3, smell of 8.7, taste of 8.7 and texture of 8.5. and the amount of fuel used was 6.03 kg. Keywords: Catfish, Coconut Fiber, Smoked, Wood Charcoal.